Epidemiology and outcome of COVID-19: experience at a private set-up in Bangladesh - Saha, Debasish Kumar; Saha, Madhurima; Bala, Chandra Shekhar; Sutradhar, Pankaj Kanti (BIRDEM Medical Journal, 2020)
Background: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has induced a sense of panic around the world. Bangladesh has also reported several hundred thousand COVID-19 patients with several thousands of deaths. SARS-CoV-2 infects people of all ages. This virus is very notorious in terms of varied presentations, severity and outcome. This observational study was done to evaluate the demography, presentation and outcome of COVID-19 patients admitted in a private hospital of Bangladesh. Methods: This prospective observational study was conducted over a period of six months. All patients in this study were positive for SARS-CoV-2 by polymerase chain reaction (PCR) and admitted to the hospital with variable presentation ranged from cough and fever to respiratory distress and pneumonia, multiple organ failure. As per the protocol, the patients were regularly evaluated for several parameters of COVID-19 related pathology. The management strategy included standard of care (SoC) and administration of antiviral drugs as per national guideline on clinical management of COVID-19, Bangladesh (Version -7). Patients’ outcome was also measured in term of recovery, transferred to higher center and death. Results: Out of total 125 patients, 60% were male and 40% female. The average age of study population was 56.8±13.8 years. Diabetes mellitus (DM) was the most common co-morbidity (62.4%). Hypertension (HTN) was present in 57.6% and ischemic heart disease (IHD) in 15.2% cases. Regarding the presenting complaints, fever was the most common (94.4%), followed by cough (84.0%) and dyspnea (43.2%). Majority (43.2%) was moderate cases, followed by severe case (28.0%), mild case (21.6%) and critical case (4.8%). Three (2.4%) asymptomatic patients were also admitted. The minimum duration of hospital stay was 1 day with maximum of 27 days. The mean duration of hospital stay was 9.8±5.4 days. Recovery was observed in 111 (88.8%) patients. Four (4.8%) patients were transferred to higher center and 8 (6.4%) patients died. Conclusion: It was observed that most of the COVID-19 patients can be adequately managed by SoC management with drug support. However, early diagnosis and hospitalization with adequate care may be important variables for better survival. Birdem Med J 2020; 10, COVID Supplement: 12-17